The role of ACE3 in Drosophila chorion gene amplification. - Orr-Weaver, T L (1989)
ACE3, an amplification control element for the third chromosome chorion cluster of Drosophila melanogaster, was identified previously as a cis-regulatory element for amplification of transposons containing the three chorion genes s18, s15 and s19. The deletion defining ACE3, located from -620 to -190 bp upstream of s18, disrupted both amplification and s18 transcription, suggesting that ACE3 might contain a transcription enhancer that regulated replication, as had been observed in a number of eukaryotic viruses. We show here that transcription control can be separated from replication control in delineating ACE3 to a 320 bp region. Addition of heterologous enhancers fails to activate amplification in tissues other than the follicle cells. Therefore ACE3 does not appear to be analogous to a transcription enhancer. However, further deletions within the ACE3 region revealed that it contains multiple functional domains. In addition, ACE3 functions independently of orientation with respect to other chorion sequences, and can be moved 1.5 kb away from other chorion sequences without eliminating amplification.